DESAIN DAN IMPLEMENTASI PEMODELAN DATABASE INDUSTRI KECIL MENENGAH KOTA PALEMBANG - Firamon Syakti; Hutrianto -; Usman Ependi (Jurnal Informatika, 2019)
The focus of this research is to design and implement a small medium industry database for the Palembang City Government. The database needs of small and medium industries due to the unavailability of data quickly and accurately when it requires information by the Department of Industry in policy making. The design and implementation of the IKM database has stages carried out starting from the needs analysis, database formation, information modeling, dashboard manufacturing, to testing. The resulting dashboard can provide data in the form of graphs and tables relating to small and medium industries either through the criteria of the region or type of industry. The layout and presentation of the data has been validated using a heuristic evaluation approach involving three experts. The validation results show that all experts agree that the results of the design and implementation of small medium industry databases do not have usability problems as evidenced by the results of the average expert testing giving a value of 0.Keywords—Database, heuristic evaluation, industry, IKM